Mediale Erinnerungsbilder im gegenwärtigen deutsch-polnischen Diskurs um Vertriebene - Kaczmarek, Dorota (Stylistyka, 2020)
The aim of the article is to answer the following research questions: (1) Which memory images can be reconstructed in the binational discourse about expulsions? (2) Which processes of linguistic realisation do they undergo? (3) How are they discursively negotiated? The focus is thus placed on the act of talking about memory in press texts in the understanding of WojciechChlebda (2012), where media actors are ‘observers’ and ‘narrators’ of memory (cf. Chlebda 2012: 111), and memory im- ages (re)constructed by them differ both with respect to the way of talking about the subject of memory and about the content of memory. The standpoint represented in this article is that in the discourse about expulsions, German and Polish memories interact with each other as two separate, oppositional memories, which are determined by differing collective knowledge about the past. Collective memory is understood as knowledge about the past shared and linguistically negotiated by a certain community; the past that undergoes certain processes of reconceptualisation, which is influenced by various social, political and media factors (cf. Czachur 2016a: 89–90). Thanks to such an approach to the research questions mentioned at the beginning, the following article is part of the research programme dealing with interdisciplinary linguistics of memory, postulated i.a. by WaldemarCzachur (2018: 44–48). Firstly, the aim is to distinguish memory images activated by the discourse. In the analysed corpus, these memory images are (a) historical memory and memory about the historical truth(b) memory about expulsions and lack of memory about expulsions (delegitimisation of the subject of memory) and (c)institutionalised, politicised memory. Secondly, linguistic and discursive characteristics of the above mentioned memory images, i.e. linguistic realisations of these memories in both discourses, are specified. Thirdly, on the basis of the analytic tools developed i.a. by German discourse linguistics, reproducible interpretative patterns are formulated. These patterns shall be understood, respectively, as a questioning of the existing concept of ‘victim’ (Chapter 4.1), delegitimisationof the key discourse notion of ‘expulsion’ (Chapter 4.2), as well as metaphorical con- ceptualisation of remembrance as a ‘fight,’ ‘battle,’ or ‘war’ (Chapter 4.3). Fourthly, linguistic and discursive practices that create conflict between both discourses of memory are described on that basis.